PENERAPAN METODE KOOPERATIF TIPE TPS DALAM PENINGKATAN MOTIVASI DAN PARTISIPASI SISWA SERTA KUALITAS HASIL BELAJAR MATEMATIKA DI SMK NEGERI 1 BALIKPAPAN - Sigit Purwanto (Universitas Islam Balitar, 2015)
This study investigates how Think-Pair-Share techniquesimprove motivation and students ’ participation in learningmathematics. The design of this study is classroom actionresearch implementing four phases: planning, implementing,observing, and reflection. The subject of this study is the XIIgrade students of Multimedia Department of SMKN 1Balikpapan. This study implements three cycles where everycycle has two meetings. Data are collected using observationand test conducted at the end of every cycle. The study showsthat learning activities in every cycle improve. The averagescores in the every cycle shows that 45.8, 80,9 and 89,5respectively in cycle I, cycle II, and cycle III.